Da irrelevância do mercado relevante: economistas, teoria econômica e política antitruste no Brasil - Onto, Gustavo Gomes (2009)
This dissertation aims at analysing the social construction of antitrust policy in Brazil, focusing on the role of economists and their theories in the organizational practice of the Administrative Economic Defence Council (CADE). Based on contemporary economic sociology, the research traces the institutional history of the policy and the antitrust agency arguing that the economic knowledge, when used and institutionalized in the agency, transforms into economic issues the judicial decisions and builds up a powerful performative tool of economic theory. The dissertation tries to emphasize the political performative economization process implicit in the isomorphic construction of economic policies around the world